Sistem Pendukung Keputusan Pemantauan Stok dan Restok Otomatis Berbasis Web - Wibisono, Bagas; Sanjaya, Ucta Pradema (Jurnal Algoritma, 2025)
Problems in stock management are often caused by delays in monitoring and the absence of a system that provides accurate restock recommendations. This study designs and implements a web-based decision support system to monitor stock and recommend restocks automatically, using the Laravel Framework. This system applies rule-based logic by considering remaining stock, average daily sales, and delivery time. The calculation process compares available stock with minimum requirements predicted from historical sales patterns. The development methodology follows the Waterfall model. The implementation results show that the system is able to accelerate the monitoring process and provide accurate restock notifications, as well as support managerial decision making in product distribution. This system also succeeded in reducing the number of expired goods to only 2%, which shows an increase in distribution efficiency. An informative dashboard interface also makes it easier to monitor stock conditions in real time. This system makes a real contribution to improving the efficiency and accuracy of inventory management.